Evaluation of Knowledge and Practices of Nurses in Orthopedic wards concerning femur Fractures - Gourgees, Samira (Iraqi National Journal of Nursing Specialties, 2005)
Objective: To evaluate the knowledge and practices of nursing staff at the orthopedic wards relative tonursing care presented to patients with femur fractures.MethodologyThe sample consisted of (50) staff nurses was selected out of orthopedic wards of fiveteaching hospital in Baghdad city for duration 15th Nivember 2001-15th of January 2002.For the purpose of data collection, two instruments were constructed. First, observationalchecklist for the practices measurements and second, knowledge test for the evaluation of the nurseknowledge. Such construction was employed through literature review and validity expert’s responses.Data were analyzed through the application of descriptive data analysis (frequency, percentage, standarddeviation, mean of scores and the inferential data analysis (Pearson correlation coefficient, one-wayanalysis of variance, t-test and LSD).Results The findings indicated that there was no significant between nurses knowledge and their nursingcare, years of employment, years of experience and training courses, but, there was significantrelationship between their knowledge and education only. The study concluded that there was nosignificant relationship between the nurses practices and their years of employment, education, andtraining courses, but, significant relationship was found between their practices and years of experience.Recommendations :The study recommended that the numbers of staff nurses should be increased,education and training programs for the nurses should be evaluated and periodic evaluation measures forthese nurses should be constructed